PENGARUH MEDIA SOSIAL TIKTOK TERHADAP PERILAKU SOSIAL MAHASISWI PAPUA DI ASRAMA PUTRI USU - Hosio, Novalin; Ritonga, Fajar Utama (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
TikTok is an application where users often share short music videos which result in and influence the social behavior of its users, both positive and negative. Almost all Papuan female students who live in the USU women's dormitory are addicted to the social media TikTok. This can be seen from their social behavior. Through the social media TikTok, the students who used to be open, often socializing with each other have now become introverts who prefer to be alone in their lives. room, taking up time to do campus assignments. This research aims to find out and see the level of influence of the social media TikTok on the social behavior of Papuan female students in the USU girls' dormitory. This research uses primary data obtained from social media TikTok on social behavior through observation and distribution of questionnaires. The sampling technique used is Proportional Multistage Random Sampling, the researcher took the entire sample in this study with a sample size of 40 respondents. The indicators used in variable X (Social Media) are dance, scroll reels and live streaming. while the indicators for variable Y (Social Behavior) are gathering, sharing, communicating, collaborating and expressing oneself. From the two indicators above, the results show that TikTok has a very strong influence on social behavior. It can be seen from the results of the correlation test that social media has carried out that it has a contribution of 62.2% to the social behavior of Papuan students in the USU girls' dormitory.